2009
DOI: 10.1007/s00726-009-0397-6
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of membrane stability and its related proteins in the tolerance of peach fruit to chilling injury

Abstract: Proteome patterns in peach fruit (Prunus persica L.) stored at different low temperatures were examined in order to gain a better understanding why peach fruit is less prone to chilling injury when stored at 0 degrees C than at 5 degrees C. Some differently expressed proteins in peach fruit stored at 0 and 5 degrees C were identified using electrospray ionization quadrupole time-of-flight tandem mass spectrometry. Among these proteins, four membrane stability related proteins, i.e., enolase, temperature-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 40 publications
6
44
0
1
Order By: Relevance
“…Similarly, accumulation of Put was also observed in chilling‐injured tomato and pepper fruit, and the induction of Put by heat‐treatment associated with increased resistance to chilling has also been previously reported in several chilling‐sensitive fruit . It is well known that maintenance of membrane stability at low temperature is important for plant resistance to cold stress . Because of the polycationic nature at physiological pH, PAs can bind strongly to anionic sites in cellular components stabilising the membranes and in turn alleviate CI .…”
Section: Resultsmentioning
confidence: 53%
“…Similarly, accumulation of Put was also observed in chilling‐injured tomato and pepper fruit, and the induction of Put by heat‐treatment associated with increased resistance to chilling has also been previously reported in several chilling‐sensitive fruit . It is well known that maintenance of membrane stability at low temperature is important for plant resistance to cold stress . Because of the polycationic nature at physiological pH, PAs can bind strongly to anionic sites in cellular components stabilising the membranes and in turn alleviate CI .…”
Section: Resultsmentioning
confidence: 53%
“…By this technique, thaumantin-like proteins [7] and proteins involved in stress response [8] were postulated as playing roles in the protection against CI. Moreover, proteins involved in membrane stability were identified [9], reinforcing the role of lipid unsaturation in the acquisition of chilling tolerance in peach fruit [10], [11].…”
Section: Introductionmentioning
confidence: 79%
“…Interestingly, peach fruit is less prone to chilling injury when stored at 0°C than at 5°C (Zhang et al, 2010). Further study using proteomics approach indicated that several membrane stability related proteins were enhanced, while proteins related to phenolic compounds metabolization were repressed in peach fruit at 0°C relative to 5°C.…”
Section: Proteome-level Responses Of Fruits To Storage Environmentsmentioning
confidence: 99%
“…Further study using proteomics approach indicated that several membrane stability related proteins were enhanced, while proteins related to phenolic compounds metabolization were repressed in peach fruit at 0°C relative to 5°C. Other proteins involved in sugar metabolism and energy pathways were decreased at 0°C, resulting in the lower assumption of sugars which has several beneficial effects in protecting plants against stresses (Zhang et al, 2010). When stored at LTs, 55 proteins from bell pepper ( Capsicum annuum ) fruits were identified as having differential abundances.…”
Section: Proteome-level Responses Of Fruits To Storage Environmentsmentioning
confidence: 99%
See 1 more Smart Citation